"A canvas of endless extent": Granville Bantock, Robert Southey and The Curse of Kehama Project. Issue 2 (3rd March 2016) - Allis, Michael
ABSTRACT: This article focuses upon the little-known musical refiguring of Robert Southey's The Curse of Kehama by the British composer Granville Bantock (1868–1946). After noting parallels between the poet and composer's creative difficulties associated with their respective projects, and issues highlighted in the reception of both "texts, " two aspects of Bantock's project (a significant document in the reception of Southey's poetry) are discussed in more detail: his attempts to unify an extended musico-poetic structure, and his response to the sense of "other" in Southey's poem. In terms of the latter, and in the context of Bantock's complex relationship with the East, two specific ideas from Southey scholarship – the concept of layers of otherness in Southey's poetry and the panoramic mode – are identified as having a real potential in helping us to understand Bantock's refiguring. The application of these ideas in a musical context offers further parallels and contrasts between poet and composer, leading to a richer understanding of the complexities involved in creative responses to oriental material in literary and musical forms.